Momok Ketimpangan: Waktu, Sejarah, Antropologi & Modernitas - Ismail F. Alatas (Antropologi Indonesia, 2009)
This article critically observes the modern regime of time that led to the temporalizing of history. The employment of the master category of singular modernity encompasses its capacity for unifying all singularities, hence, betraying capitalism's and nation states' desire to transform plural histories into a single one. Anthropology too has been responsible for the production and maintenance of the temporal order of modernity. While capitalist and national expansions would use violent means to spatially establish themselves by destroying alternative modes of production and body politics, anthropology manipulates time with various devices of sequencing and distancing thereby assigning the conquered into the past. This article suggests that anthropology should no longer align itself with modernity and its notion of human progress. Rather, it should play out disqualified forms of interpretations, rescuing the multiple temporalities at work in the world, to blast the continuum of history. Key words: Time, History, Anthropology & Modernity